Oppurtunistic Routing Through Delay Analytical Methods in Ad-Hoc Wireless Networks - Thenmozhi, M; Tamilarasi, N (International Journal of Computer Sciences and Engineering, 2025)
Many researchers are showing a keen interest in opportunistic routing and are becoming very popular. This is mainly due to its specific characteristic that it posses for improving the performance and efficiency of the wireless ad-hoc networks. A broadcasting feature of wireless ad-hoc networks is made use in opportunistic routing which increases the network's overall reliability and throughput. This research paper focuses on an efficient analytical model which is capable of transmitting the data packets both in known and unknown topologies. This is done by making use of single and multiple forwarders. The proposed approach is designed in such a way that it reduces the probability of packet loss in the network. Furthermore this paper concentrates on the security aspects of the network and provides a proper authentication mechanism before the data packets are delivered to the receiver.